Postural-motor development, spinal range of movement and caregiver burden in Prader-Willi syndrome-associated scoliosis: an observational study - Maria Chiara Maccarone; Mariarosa Avenia; Stefano Masiero (PAGEPress Publications, 2024)
Prader-Willi syndrome (PWS) is a rare genetic disorder characterized by hypothalamic dysfunction, hypotonia, cognitive deficits, and hyperphagia, primarily resulting from genetic abnormalities on chromosome 15. Among its varied manifestations, musculoskeletal issues, notably scoliosis, pose important challenges in management. This study aims to investigate differences in postural-motor development and spinal range of movement between preadolescents and adolescents with PWS, with and without scoliosis, while also exploring the potential impact of scoliosis on caregiving burden, an aspect yet to be thoroughly explored in existing literature. This observational study evaluated 13 individuals diagnosed with PWS, including 5 with scoliosis (PWS-Sc) and 7 without (PWS-NSc). Inclusion criteria comprised ages 8 to 18 years, confirmed PWS diagnosis through genetic testing, and scoliosis diagnosis. Anamnestic data, physical examinations, and surface measurements were collected, along with parental burden assessments using the Zarit Burden Interview (ZBI). Both groups displayed delays in achieving postural-motor milestones, with the PWS-Sc group exhibiting a more pronounced delay, although statistical significance was not achieved. The main curve magnitude in the PWS-Sc group averaged 31.5° Cobb, with 60% of cases presenting an S-shaped curve. Surface measurements of physiological curves did not differ significantly between groups, but the scoliosis-affected group exhibited lower lumbar extension values (p=0.04). The overall ZBI revealed higher scores in the PWS-Sc group, although statistical significance was not reached. However, significant differences were observed in single questions score evaluating aspects such as social life and caregiver uncertainty (p=0.04 and p=0.03, respectively). Despite the small sample size, delays in achieving postural-motor milestones, particularly in individuals with scoliosis, were observed. The differences recorded in lumbo-pelvic movement suggest that tailored interventions may be beneficial. The heightened caregiving burden in the scoliosis group underscores the need for targeted support. Early intervention and ongoing monitoring should be important for accurate diagnosis and appropriate care, potentially with psychological support for caregivers.